(untitled) (Scientific journal of the Fergana State University, 2023)
This article highlights the issues of proper organization of educational and extracurricular time of students as a socio-pedagogical necessity of educating schoolchildren in discipline and education.The conditions for the rational organization of educational activities are a continuous process of disciplining children. In order to understand the inner content of the adolescent’s actions, it was justified the need to change his psychological characteristics in relation to his activities.